PENEGAKAN HUKUM TINDAK PIDANA INSUBORDINASI DALAM MILITER (STUDI KASUS PUTUSAN PM NOMOR: 94-K/PM.III-12/AD/VI/2015) - Anuar Bukhari; Muhammad Abudan (Fakultas Hukum Universitas Tarumanagara, 2019)
Insubordination is a criminal act against a superior committed by a TNI soldier, during office hours or outside office hours on condition that the superiors get an official order to carry out their duties or represent the company unit. Insubordination crimes is an act that is not justified among the military, because it is considered to have violated the Sapta Marga and oath of warriors which are the basis of personality patterns as TNI soldiers. In this research, there are a several of issues, first about what is an insubordination crime, and the second is how law enforcement and judges considerations in deciding an insubordination case. The research method used by the author is normative legal research. The results of the study found that law enforcement of TNI soldiers committing an insubordination criminal act is the same as law enforcement of other criminal acts carried out by military members, what distinguishes it is the court's power in the matter of prosecuting at the first level, if the defendant is a Captain down to be tried through a Military Court. Meanwhile, the defendants with the rank of Major and above were tried through the High Military Court. Judges' considerations in deciding on this insubordination case are guided by Articles 103 to 109 of the Indonesian Military Penal Code, as well as the evidence gathered in the trial, in addition, thoroughness, carefulness, and wisdom of the judge is also highly prioritized, to avoid making mistakes in decision.